Kompetensi Absolut Pengadilan Tata Usaha Negara Setelah Lahirnya UU No 30 Tahun 2014 (Berdasarkan Undang-Undang No. 30 Tahun 2014 & Undang-Undang No. 5 Tahun 1986) - Stevania Stevania; Rasji Rasji (Journal on Education, 2022)
Absolute competence analysis on Government Administrative Law and State Administrative Court Law. Absolute competence is the authority of the court to adjudicate a case or dispute in the form of object, material or subject matter of the dispute. The wider the absolute competence that the object in dispute is not only a state administrative decision but there are factual or real actions. The birth of government administration laws brought many changes, namely in the form of absolute and relative competence. In the law on government administration, it is regulated that government administrative actions are the object of dispute, there is a theoretical and conceptual side that expert opinion disagrees with the enactment of this factual action. Enforcement of this factual action has become a lot of disputes between law enforcers in determining law violations committed by state institutions. With the addition of the object of dispute in the state administrative court, several disputes have arisen between the government administration law and the state administrative court law. Factual actions have various meanings that can lead to abuse of authority and can make people and government agencies confused. In the KTUN in the judicial law.